Dashboard to Monitor Performance of an Hotel in the Financial Perspective - Ana Margarida Santos Lavrador; Laureano, Raul M. S. (2019 14th Iberian Conference on Information Systems and Technologies (CISTI), 2019)
Companies in a very competitive environment need to analyze the data generated by the business quickly, intuitively and easily read. Thus, dashboards, a form of reporting that allows the monitoring of indicators relevant to the business, it has become popular among managers. In this context, this article focuses on monitoring the performance of the Hotel Resort& SPA, from the perspective of its financial officer. To this end, two models of dashboards for hotel finance managers are proposed based on good practices identified in the literature. Interviews with experts allowed the identification of key performance indicators and ensured that dashboards are effectively useful for decision-making. Thus, this study contributes to helping financial managers, related to hospitality, in decision making by providing two types of dashboards. In addition, it contributes to the knowledge by identifying relevant KPIs, from the perspective of the financial management of hotels, and making known the dashboards, specifically elaborated in the perspective of the use by these professionals.